The Role of Local Government Policies in Simultaneous Village Head Elections - Muhadam Labolo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the modern state administration system, it is no longer necessary to maintain village government as it is now because it is very outdated. The Indonesian people currently need an autonomous modern region, where the village is given the right to determine and manage its household. This can be done through direct village head elections. Law No. 6 of 2014 concerning villages still implies the need for local government intervention in determining regulations and policy directions for village head elections, especially those carried out simultaneously. Therefore, this study aims to examine the role of local government policies in implementing simultaneous village head elections in Indonesia. This study uses a descriptive qualitative approach with secondary data sources through library research. The results of the study found that the role of the government in implementing the policy of simultaneous village head elections was significant where the local government had a dual function, namely as a policymaker, organizer, and supervisor and a place to settle village head election disputes simultaneously. It can also be concluded that the village head election is not free from conflicts of interest, so the local government must also be fair and neutral and not take sides with any of the candidates.